Bladder Cancer to Patients Younger than 30 Years: A Retrospective Study and Review of the Literature. Issue 4 (October 2017) - Katafigiotis, Ioannis; Sfoungaristos, Stavros; Martini, Alberto; Stravodimos, Konstantinos; Anastasiou, Ioannis; Mykoniatis, Ioannis; Duvdevani, Mordechai; Constantinides, Constantinos
Objectives: The aim of this report was to study the specific characteristics of bladder cancer in patients younger than 30 years. Materials and Methods: Five patients with a mean age of 24 ± 2.83 years were included in the study. All patients had painless macroscopic hematuria as the first symptom. Three patients had pTa as a first diagnosis, one had pT1 and one pT2. All the patients had smoking as a risk factor and at least one additional possible risk factor. Results: One patient with pTa had an aggressive course and after multiple recurrences was diagnosed with pT2 and refused to be submitted to radical cystectomy and died from the disease even though he received a multimodality treatment. The other two patients with the pTa diagnosis had no recurrence after the first TUR-BT and the patient with the pT1 diagnosis after one recurrence with a pTa histology is free of recurrence for the last 2 years. The patient diagnosed with pT2 was submitted to a radical cystectomy and an s-pouch diversion with a preservation of the genital system in order to have the ability of a future motherhood with the acceptance of course risks. Conclusions: Young patients with bladder cancer is a difficult group of patients and show more reluctance to comply to the necessary strict follow-up of the repeated urinary cytology examinations, cystoscopies and CT pyelographies. Herein, we report a retrospective study of five patients younger than 30 years with bladder cancer.